EFISIENSI ALOKASI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI PADA USAHA BUDIDAYA UDANG VANAME - Heru Wahyudi; Muhiddin Sirat; Emi Maimunah; Muhammad Rizky Refianto; HERU WAHYUDI (Business, Economics dan Entrepreneurship, 2022)
The purpose of the study was to analyze the efficiency of the allocation of the use of production factors in the vannamei shrimp farming business. The data used is cross-sectional data in 2020 in East Rawajitu District. The variables used were the number of fry, labor, feed, lime, and land area. The analytical tool used is simple regression, namely Ordinary Least Squares (OLS). The results showed that the number of fry, labor, feed, lime, and land area had a positive and significant effect on vaname shrimp production. The production factors used in the vannamei shrimp business have not been efficient in terms of allocation and have not been optimal. Keywords: Allocation Efficiency, East Rawajitu, Ordinary Least Squares (OLS), Vaname Shrimp.